Systematic Review on Ear Identification - Alemran, Ahmad; Binti Rahmatullah, Bahbibi; Hadi, Ali (International Journal of Engineering and Technology, 2018)
Context: The topic is permitted from modern topics of interest for researchers to find logical solutions to problems of detection and recognition for ear identification. Therefore, we are looking for a solution to the problem of occlusion, detection and recognition of the person create an integrated system based on the latest research and to find new results in terms of accuracy and time and be comprehensive for everything.Objective: To survey researchersâ€™ efforts in response to the new and disruptive technology of ear identification systems, mapping the research landscape form the literature into a coherent taxonomy.Method: We use a systematic review as the basis for our work. a systematic review builds on 249 peer-reviewed studies, selected through a multi-stage process, from 1960 studies published between 2005 and 2017.Results: We develop a taxonomy that classifies the ear identification systems. The results of these articles are divided into three main categories, namely review and survey article, studies conducted on ear biometrics and development of ear biometric applications.Conclusion: The paper is, to our knowledge, the largest existing study on the topic of ear identification. This typically reflects the types of available systems. Researchers have expressed their concerns in the literature, and many suggested recommendations to resolve the existing and anticipated challenges, the list of which opens many opportunities for research in this field.Â Â